2021
DOI: 10.1002/leap.1426
|View full text |Cite
|
Sign up to set email alerts
|

Philosophers' perceptions of pay to publish and open access in Spain: Books versus journals, more than a financial dilemma

Abstract: This study examines habits and perceptions related to pay to publish and open access practices in fields that have attracted little research to date: philosophy and ethics. The study is undertaken in the Spanish context, where the culture of publication and the book and journal publishing industry has some specific characteristics with regard to paying to publish, such as not offering open access distribution of books published for a fee. The study draws on data from a survey of 201 researchers, a public debat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Half of these authors covered APCs with research funds. A subsequent study among a sample of philosophers (Feenstra & Delgado L opez-C ozar, 2022) concluded that they were reluctant to pay APCs since author fees raised doubts and suspicions about the potentially distorting effects on two issues reviewed below: equality of opportunity for authors and the integrity and quality of manuscript evaluation systems.…”
Section: Authors' Views and Behaviour Regarding Apcsmentioning
confidence: 99%
“…Half of these authors covered APCs with research funds. A subsequent study among a sample of philosophers (Feenstra & Delgado L opez-C ozar, 2022) concluded that they were reluctant to pay APCs since author fees raised doubts and suspicions about the potentially distorting effects on two issues reviewed below: equality of opportunity for authors and the integrity and quality of manuscript evaluation systems.…”
Section: Authors' Views and Behaviour Regarding Apcsmentioning
confidence: 99%
“…Regarding relevant studies related to Spain, there are articles analysing open access editorial practices (Melero et al, 2017), perceptions towards open access (Ruiz‐Pérez & Delgado‐López‐Cózar, 2017), to open access and peer review (Segado‐Boj et al, 2018), towards open science (Rodríguez‐Bravo & Nicholas, 2021), and recently with a focus on philosophy (Feenstra & López‐Cózar, 2022) and drivers and barriers in the transition to open science (González‐Teruel et al, 2022). The aim of this paper is to examine and analyse perceptions and editorial practices related to open access, preprints, underlying data and open peer review, from the perspective of editors of scientific journals published in Spain.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, OAI , which had an increasing main effect on the negativity, showed reducing effects in the interaction with gender and tweeter roles (except for Academicians and Scholars ). This is in line with our existing knowledge about the OAI as a double-edged sword in OA issues: while the citation advantage is considered one of the OA benefits (Ciriminna et al ., 2021), there exist concerns about the impact and prestige of OA journals (Feenstra and López-Cózar, 2021; Nagaraj and Bhandi, 2017; Togia and Korobili, 2014). This is also true for OAM .…”
Section: Discussionmentioning
confidence: 99%